Efeito do cetoprofeno intravenoso na percepção da dor até uma hora após histeroscopia diagnóstica em pacientes sob sedação venosa no centro cirúrgico da Maternidade-Escola Assis Chateaubriand - Serpa, Ana Kelly Lemos (2019)
Objective: To evaluate the effect of intravenous ketoprofen on pain perception after 15, 30, 45 and 60 minutes after diagno stic hysteroscopy under venous sedation with fentanyl and propofol. Methods: Prospective clinical trial with 60 women aged 18 to 75 years, physical status ASA I and ASA II, submitted to diagnostic hysteroscopy under venous sedation at the Assis Chateaubria nd School Maternity Surgical Center. A group of 30 patients received 100mg intravenous ketoprofen 30 minutes before venous sedation with propofol and fentanyl. A second group of 30 patients received propofol and fentanyl sedation without intravenous ketopr ofen. Results: After 15 minutes of hysteroscopy, pain perception in the group receiving ketoprofen was: 22 patients did not report pain; 6 patients experienced mild pain; 1 patient had moderate pain; 1 patient with severe pain. In the group not receiving k etoprofen: 20 patients did not report pain; 7 patients had mild pain; 2 patients experienced moderate pain, 1 patient had severe pain. After 30 minutes, in the ketoprofen group: 27 patients reported no pain; 2 patients experienced mild pain; 1 patient expe rienced severe pain. In the group not receiving ketoprofen: 21 patients did not report pain; 5 patients had mild pain; 4 patients experienced moderate pain; no patient with severe pain. After 45 minutes, in the ketoprofen group, no patient experienced pain . In the group that did not use ketoprofen: 22 patients did not report pain; 4 patients had mild pain; 3 patients experienced moderate pain; 1 patient had severe pain. After 60 minutes, in the ketoprofen group, the 30 patients experienced no pain. In the g roup not receiving ketoprofen: 26 patients reported no pain; 4 patients experienced mild pain; no patient had moderate or severe pain. Conclusion: The use of 100mg intravenous ketoprofen 30 minutes before venous sedation with fentanyl and propofol for diag nostic hysteroscopy does not lead to a decrease in pain intensity perception 15, 30, 45 and 60 minutes after the procedure. Keywords: Diagnostic hysteroscopy; Anesthesia; Fentanyl; Propofol; Anti inflammatories.